Musical folklore as a tool for social-ecological change in the Colombian Caribbean - López-Angarita, Juliana; Restrepo, María del Pilar; Guzmán, Katherine; Escobar, Dairo (Frontiers in Conservation Science, 2022)
Large herbivorous fishes, such as parrotfishes, play a critical role in coral reef ecosystems by limiting the coverage of macroalgae. Yet, in the Colombian Caribbean, parrotfishes are being increasingly targeted for human consumption as the demand for fish increases with tourist numbers. The Colombian Caribbean is dominated by Afro-descendant communities, and music is a deeply rooted form of expression and communication. ‘Champeta’, the local music folklore, is heard at all times of day and danced continuously in the islands off the coast of Cartagena. We conducted a survey of local tourist and fisheries stakeholders to characterise the parrotfish fishery, and designed a contextualised awareness-raising campaign of the ecological role of parrotfish and the need for management in the Islands of the Corales del Rosario and San Bernardo National Park. In doing so, we test if Champeta could be used as a mechanism for social-ecological change in Caribbean coastal communities in the context of coral reef conservation. Locals were engaged in every aspect of the campaign, especially with the song, as the campaign was a process rooted in their culture, interests and idiosyncrasies. Surveys of restaurants illustrated the size of the fishery and the extent of misinformation surrounding the consumption of parrotfish by tourists. We found that both locals and tourists held misconceptions about the ecological role of parrotfish and were supportive of efforts to protect them.